Catheters linked thrombosis in neonates: a single center observational study - Marwa Mohamed Farag; Hesham Abd El Rahim Ghazal; Mohamed Masoud Radwan; Nada Saeid El-sayed (BMC, 2024)
Abstract Background Central venous catheters (CVCs) are the major risk factors for neonatal thrombosis that might negatively affect morbidity and mortality in neonates. The aim of the present work was to estimate the incidence of CVC-linked thrombosis, among neonates in the NICU of Alexandria University Maternity Hospital, Egypt, over 1year, and to determine its possible risk factors. Methods This observational cohort study involved 134 newborn infants born from July 2020 to July 2021with CVCs insertion during their hospital stay. Patients who had congenital anomalies, had thrombosis unrelated to the implantation of CVCs or died before 7 days of catheter placement were excluded from the analysis. The 134 neonates who met the study's eligibility requirements had 142 CVCs inserted. Serial ultrasound and Doppler scans on site of venous insertion of catheters were performed. Results Seventeen patients with catheter's thrombosis (12%) were found during the placement of 142 catheters or 1615 CVCs' days, resulting in an overall rate of 10.5 thrombotic events per 1000 catheters' days. We constructed a logistic regression model to identify risk factors behind CVC-linked thrombosis. In univariate analysis, femoral central venous lines (CVLs), catheter dwell-time, sepsis, packed red cells (PRBCs) transfusions and low platelet count were risk factors for CVC-linked thrombosis. Nevertheless, only PRBCs transfusion was significant in the multivariate analysis, with OR and 95% confidence level 5.768 (1.013-32.836). Conclusion Many factors should be considered in prediction of patients at risk of thrombosis including sepsis, femoral line insertion, low platelet count and PRBCs-transfusions. In our analysis, PRBCs-transfusion through peripheral intravenous lines (PIVs) was the strongest factor associated with CVC-linked thrombosis.